Breaking beautiful - Wolf, Jennifer Shaw (Walker, 2012)
Allie is overwhelmed when her boyfriend, Trip, dies in a car accident, leaving her scarred and unable to recall what happened that night, but she feels she must uncover the truth, even if it could hurt the people who tried to save her from Trip's abuse.